Concept «fair balance» in the practice of the European Court of Human Right - Blazhivska, Nataliia (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
The article is devoted to the disclosure of the concept of «fair balance» in the practice of the European Court of Human Rights. There are analyzed the latter’s decision concerning the application of Article 1 of the First Protocol to the Convention for the Protection of Human Rights and Fundamental Freedoms regarding the observance by the respondent state of a fair balance between the society interests and the protection of the individual’s private interests. In the article on the basis of the analysis of the European Court of Human Rights practice in the subject there is concluded that the violation of the aforesaid fair balance takes place mainly in the absence of adequate compensation for the damage caused by the restriction of ownership.